2013
DOI: 10.1021/es403847h
|View full text |Cite
|
Sign up to set email alerts
|

Increased Biomass Burning Due to the Economic Crisis in Greece and Its Adverse Impact on Wintertime Air Quality in Thessaloniki

Abstract: The recent economic crisis in Greece resulted in a serious wintertime air pollution episode in Thessaloniki. This air quality deterioration was mostly due to the increased price of fuel oil, conventionally used as a source of energy for domestic heating, which encouraged the residents to burn the less expensive wood/biomass during the cold season. A wintertime sampling campaign for fine particles (PM2.5) was conducted in Thessaloniki during the winters of 2012 and 2013 in an effort to quantify the extent to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
88
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 53 publications
18
88
1
9
Order By: Relevance
“…Finally, it is noteworthy that while the mean value of AOD for 2014 in the period summer-autumn is the lowest recorded since 1994, the corresponding value for the period winter-spring is the highest of the last 7 years. These very high AOD values are probably due to the increased biomassburning aerosols arising from a shift in the type of fuel owing to the economic crisis in Greece after 2009 (Saffari et al, 2013). As a consequence of the increased aerosols, the levels of irradiance at 350 nm for winter-spring 2014 are the lowest recorded during the last decade.…”
Section: The Role Of Ozone and Aerosols On Short-and Long-term Variabmentioning
confidence: 99%
“…Finally, it is noteworthy that while the mean value of AOD for 2014 in the period summer-autumn is the lowest recorded since 1994, the corresponding value for the period winter-spring is the highest of the last 7 years. These very high AOD values are probably due to the increased biomassburning aerosols arising from a shift in the type of fuel owing to the economic crisis in Greece after 2009 (Saffari et al, 2013). As a consequence of the increased aerosols, the levels of irradiance at 350 nm for winter-spring 2014 are the lowest recorded during the last decade.…”
Section: The Role Of Ozone and Aerosols On Short-and Long-term Variabmentioning
confidence: 99%
“…Assuming that vehicular traffic is stable throughout the year (Grivas et al, 2012) and long-range transport and meteorology are similar over both sites, the increase in OC and EC during the cold season can be attributed to an additional primary source, most probably heating. In addition by examining the difference of OC and EC levels between Athens and Finokalia during the winter months for the whole period studied a notable increase during the 2011-2013 period compared to 2008-2010 is also observed (30 % in OC and 80 % in EC), mainly driven by wood burning activities that maximized during the last two winters (2011)(2012)(2013) in most Greek cities (Saffari et al, 2013).…”
Section: Estimation Of Secondary Organic Carbonmentioning
confidence: 99%
“…In Switzerland, during winter, BC from RWB contributes on average 24-33 % of measured BC levels, which is a noticeably high fraction as the contribution of wood burning to the total final energy consumption is less than 4 % (Herich et al, 2014). Saffari et al (2013) showed the connection between wood burning and increased levels of PM during the winter in Thessaloniki, while Sarigiannis et al (2014) further quantified an average increase in PM 10 (and PM 2.5 ) due to biomass burning of up to 43 µg m −3 . In Athens, the intense use of open fireplaces and woodstoves for domestic heating during the last years has caused notable increases in the ambient PM concentrations, with the contribution from biomass combustion reaching up to 70 % of the PM mass concentration during extreme pollution episodes.…”
Section: Introductionmentioning
confidence: 99%